Sailing uncharted waters with old boats? COVID-19 and the digitalization and professionalization of presidential campaigns in Portugal - Santana Pereira, J. (2023)
This article investigates the extent to which the COVID-19 pandemic fostered significant shifts in election campaigning. The argument is that COVID-19 might have had an impact on both digitalization and professionalization, which might have been regarded as necessary strategies to curb the difficulties brought about by the pandemic. We apply a most similar systems design with a threefold comparative scheme in order to capture and isolate such effects in the campaigns preceding the 2021 Portuguese presidential elections, using data from campaign spending, campaign activities, and social media activity and impact. Results show that the pandemic crisis has not, generally speaking, brought about a higher level of digitalization of electoral campaigns, in spite of online events having become more common. On the contrary, while there were signs of feebler patterns of normalization of online competition in 2021 vis-à-vis 2016, namely in terms of engagement, normalization was stronger after the lockdown than before. Lastly, relative investment in professionalization was similar in 2016 and 2021, and the difference between the budgeted and the actual investment in 2021 cannot be attributed to the worsening of the pandemic situation or to the lockdown. In sum, we depict a scenario of remarkable stability of the electoral campaigns put forward by presidential candidates in terms of digitalization and professionalization. Its possible causes and consequences are discussed.